CSR and marketing : two sides of the same coin - Mohd. Israil, Khaliq Ahmad; Abd. Manaf, Noor Hazilah; Tahir, Suziwana (2010)
The value of reputations has come to diffuse corporate diligence since the scandals at Enron, WorldCom and Qwest Communications. Aside from losing citizen‟s money, the companies lost its elusive asset namely the public trust. Hence corporate social responsibility (CSR) is increasingly becoming the tool to build the image of the corporation. That denotes building corporate eminence by ensuring superiority products and services, inspiring social accountability by exerting in an overt and lucid fashion, and avail best management practices through profuse and conscientious communication with employees, and proffer congruous training and development. CSR can link the enterprise and brand; therefore in the long run this relationship contributes to the society. The World Business Council for Sustainable Development elucidate CSR as the continuing devoir by business to demean oneself ethically and confer to economic progression while meliorate the preeminence of life of the workforce and their lineage as well as insular community and society at large. The intent of this paper is to delve into the praxis of CSR as a contrivance apprehension of a today‟s business organization. This concept paper proposes that strategic CSR is good for business and the nation and the paper advocates that marketing may take a leading role in imperative CSR exertion